Uniform Across-the-Board Promotions - Jauch, Marc-Oliver.; SpringerLink (Online service) (Cham : Springer International Publishing : Imprint: Springer, 2014)
Uniform Across-the-Board Promotions (UABPs) are characterized by retailers offering a uniform discount on the entire assortment (e.g. 20% on every article) to their customers. This latest form of promotion has gained massive popularity among retailers and consumers in recent times. This book analyses their impact on short- and long-term retailer performance and consumer shopping behaviour by applying state-of-the art marketing research methods. Furthermore this book provides guidance for retail and marketing managers on how to best profit from UABPs, to increase sales and profits while balancing the risks associated with this type of promotion.
Introduction -- Conceptual Framework -- Impact of Uniform Across the Board Promotions on Short-term Store Revenues -- Adjustment and Permanent Effects of Uniform Across the Board Promotions -- UABPs: Antecedents and Consequences on a Household Level -- Summary of Results.
Keywords: Economics; Marketing; Economics/Management Science; Marketing; Sales/Distribution/Call Center/Customer Service; Market Research